Desiccation-Driven Senescence in the Resurrection Plant Xerophyta schlechteri (Baker) N.L. Menezes: Comparison of Anatomical, Ultrastructural, and Metabolic Responses Between Senescent and Non-Senescent Tissues - Radermacher, Astrid Lillie; du Toit, Stephanus Francois; Farrant, Jill M. (Frontiers in Plant Science, 2019)
Drought-induced senescence is a degenerative process that involves the degradation of cellular metabolites and photosynthetic pigments and uncontrolled dismantling of cellular membranes and organelles. Angiosperm resurrection plants display vegetative desiccation tolerance and avoid drought-induced senescence in most of their tissues. Developmentally older tissues, however, fail to recover during rehydration and ultimately senesce. Comparison of the desiccation-associated responses of older senescent tissues (ST) with non-senescent tissues (NST) will allow for understanding of mechanisms promoting senescence in the former and prevention of senescence in the latter. In the monocotyledonous resurrection plant Xerophyta schlechteri (Baker) N.L.Menezes, leaf tips senesce following desiccation, whereas the rest of the leaf blade survives. We characterised structural and metabolic changes in ST and NST at varying water contents during desiccation and rehydration. Light and transmission electron microscopy was used to follow anatomical and subcellular responses, and metabolic differences were studied using gas chromatography-mass spectrometry and colorimetric metabolite assays. The results show that drying below 35% relative water content (0.7 gH2O/g dry mass) in ST resulted in the initiation of age-related senescence hallmarks and that these tissues continue this process after rehydration. We propose that an age-related desiccation sensitivity occurs in older tissues, in a process metabolically similar to that observed during age-related senescence in Arabidopsis thaliana.